I remember mama [videorecording (DVD)] - Stevens, George, 1904-1975; Dunne, Irene, 1898-1990; Bel Geddes, Barbara; Homolka, Oscar, 1898-1978; Forbes, Kathryn, 1908-1966 (Warner Home Video, 2004)
Portrays the struggles of a Norwegian immigrant family at the turn of the century in San Francisco.